Harsh communication: characteristics of caregivers and persons with dementia. (2nd October 2020) - Petrovsky, Darina V.; Sefcik, Justine S.; Hodgson, Nancy A.; Gitlin, Laura N.
Abstract: Objectives: While ways to reduce caregiver burden have dominated dementia care research, there is little understanding of daily communication and its relationship to caregiver burden and depression. In this study, we sought to: (1) describe the frequency of harsh communication used by caregivers; (2) examine the relationship between harsh communication, caregiver and person with dementia characteristics; and (3) determine the contributions of caregiver depression and burden on such communication. Method: Cross-sectional baseline data were drawn from 250 dyads, who participated in the Dementia Behavior Study (NCT01892579). Hierarchical linear regression models were used to examine the relationship between dyad characteristics and harsh communication scores (using the 6-item Negative Communication Scale), controlling for three groups of covariates: sociodemographic, relationship characteristics and health factors. Results: More than half of the caregivers (mean age = 65.4, 81.2% women, 45.6% spouses) reported they felt like screaming/yelling ( N = 138, 55.2%) or used a harsh tone ( N = 129, 51.6%) at persons with dementia (Mini Mental Status Examination mean = 14.3, SD: 7.8) at least sometimes. When controlling for all covariates, for each unit increase in caregiver burden, harsh communication increased by 0.486 units ( p < 0.001); similarly, for each unit increase in caregiver depression, harsh communication increased by 0.301units ( p < 0.001). Conclusion: Over half of dementia caregivers reported they felt like or used one or more harsh forms of communication. Caregiver burden and depression were incrementally associated with greater use of negative communication. Providing caregivers with knowledge, support and specific communication skills may lessen the frequency of harsh communication and possibly reduce burden and depression.